The Behavior Prevention Of Obesity In Adolescents With Self Efficacy: A Systematic Review - MarthaSari, Ni Ketut Putri; Sulistiawati, Sulistiawati; Indarwati, Retno (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Obesity is an abnormal accumulation of fat and greatly affects health, physical and cognitive, so it is necessary to do preventive behavior. The purpose of this literature study is to determine how to prevent obesity in adolescents by means of self-efficacy in adolescents. The literature search strategy identified 605 by identifying various articles in the six databases of Scopus, Science Direct, Pubmed, Proquest, Sage, and Cinahl. The most common type of research is a randomized controlled trial. The results showed several general characteristics such as the type of research, the time of evaluation, and the type of research. behaviors that can trust adolescents to do and implement obesity prevention by controlling eating behavior, doing moderate to strong physical activity (MVPA), increasing lifestyle behavior, eating patterns / nutrition, the influence of parents and school. Self-efficacy is very important in the early stages, modification and maintenance of obesity prevention behavior